The economic impact of an efficient financial futures market in the South African economy - Collings, Bryan A. C.(Bryan Alexander Coppin) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Econ.) -- University of Stellenbosch, 1993.